Granulomatous variant of giant centrifugal miliaria profunda in a hypothyroid infant: A case report - Akansha A Chadha; Sunanda A Mahajan; Atul Dongre; Uday S Khopkar (Indian Dermatology Online Journal, 2019)
The miliarias are a clinically heterogeneous group of diseases which occur when the free flow of eccrine sweat to the skin surface is impeded. Miliaria profunda is a variant with obstruction of the duct at or below the level of dermoepidermal junction. The giant centrifugal variant of miliaria profunda has been described in the past at the sites of occlusive tapes and in febrile patients. Thyroid hormone has a regulatory effect on the skin and its appendages and an association of hypothyroidism with this variant of miliaria profunda has not been described in the past. We report a case of giant centrifugal miliaria profunda in an infant with congenital hypothyroidism.